URGENSI LITERASI AGAMA DI ERA DIGITAL - Putu Dana Yasa (Sanjiwani: Jurnal Filsafat, 2023)
One of the main factors causing inter-religious debate is the lack of religious literacy. The debate about the truth of each religion becomes a spectacle in various social media networks that provide unlimited freedom for anyone to give arguments and debate openly. Responding to this development of science and technology, it is the big task of Hindu intellectuals in an effort to continue to fill Hindus with religious literacy so that the basis of Hindu beliefs becomes stronger and is not easily influenced by irresponsible elements, both externally and internally. The Hindus themselves. The purpose of this research is as an effort to provide an explanation to all religious people, especially Hindus, so that they are again aware of the importance of religious literacy in the midst of current technological advances. This research is a type of qualitative study using a philosophical approach, analyzing the conditions of Hinduism which desperately need awareness about strengthening religious literacy amidst technological advances that are developing so rapidly.